Microbiological quality water used in food production in the municipalityof family agribusinessesConstantina/RS - Volkweis, Dionara Simoni Hermes; Lazzaretti, Jordana; Boita, Elis Regina Fátima; Benetti, Fábia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The quality of water used in both the food industry and for domestic consumption must meet basic requirements for it to be deemed fit for consumption and use. According to Decree No.2,914 of December 12, 2011of the Ministry of Health, the levels of total and fecal coliforms should be absent from the smoothed samples. The water used for preparing food or even cleaning of equipment can act asviacontamination of foodwithpathogenic microorganisms. In the present study, we found water quality through laboratory analysis for the identification of Total and Fecal coliforms as indicators of fecal contamination of the water used in food production. The analyzes were performed according to standard protocols under Methodological Standard Methods for the examination of water & waste water, 22th edition, 2012. The opinions were based on reference standards according to Ordinance No.2,914, of December 12, 2011, the Ministry of Health of 10 samples analyzed 07 are unfit for use, of which 07 were contaminated by total coliforms and 03 for thermotolerant coliforms.